Activation of Nrf2 by Lithospermic Acid Ameliorates Myocardial Ischemia and Reperfusion Injury by Promoting Phosphorylation of AMP-Activated Protein Kinase α (AMPKα) - Zhang, Min; Wei, Li; Xie, Saiyang; Xing, Yun; Shi, Wenke; Zeng, Xiaofeng; Chen, Si; Wang, Shasha; Deng, Wei; Tang, Qizhu (Frontiers in Pharmacology, 2021)
Background: As a plant-derived polycyclic phenolic carboxylic acid isolated from Salvia miltiorrhiza, lithospermic acid (LA) has been identified as the pharmacological management for neuroprotection and hepatoprotection. However, the role and mechanism of lithospermic acid in the pathological process of myocardial ischemia-reperfusion injury are not fully revealed. Methods: C57BL/6 mice were subjected to myocardial ischemia and reperfusion (MI/R) surgery and pretreated by LA (50mg/Kg, oral gavage) for six consecutive days before operation. The in vitro model of hypoxia reoxygenation (HR) was induced by hypoxia for 24 hours and reoxygenation for 6 hours in H9C2 cells, which were subsequently administrated with lithospermic acid (100 μM). Nrf2 siRNA and dorsomorphin (DM), an inhibitor of AMPKα, were used to explore the function of AMPKα/Nrf2 in LA-mediated effects. Results: LA pretreatment attenuates infarct area and decreases levels of TnT and CK-MB in plasm following MI/R surgery in mice. Echocardiography and hemodynamics indicate that LA suppresses MI/R-induced cardiac dysfunction. Moreover, LA ameliorates oxidative stress and cardiomyocytes apoptosis following MI/R operation or HR in vivo and in vitro. In terms of mechanism, LA selectively activates eNOS, simultaneously increases nuclear translocation and phosphorylation of Nrf2 and promotes Nrf2/HO-1 pathway in vivo and in vitro, while cardioprotection of LA is abolished by pharmacological inhibitor of AMPK or Nrf2 siRNA in H9C2 cells. Conclusion: LA protects against MI/R-induced cardiac injury by promoting eNOS and Nrf2/HO-1 signaling via phosphorylation of AMPKα.